2007
DOI: 10.1038/sj.jcbfm.9600554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma Input and Reference Tissue Models for Analysing [11C]flumazenil Studies

Abstract: A single-tissue compartment model with plasma input is the established method for analysing [ 11 C]flumazenil ([ 11 C]FMZ) studies. However, arterial cannulation and measurement of metabolites are time-consuming. Therefore, a reference tissue approach is appealing, but this approach has not been fully validated for [11 C]FMZ. Dynamic [ 11 C]FMZ positron emission tomography scans with arterial blood sampling were performed in nine drug-free depressive patients and eight healthy subjects. Regions of interest wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 41 publications
(76 reference statements)
2
56
0
Order By: Relevance
“…Consequently, the findings of this study may not be relevant for reference tissue modelling of scans conducted within a few days of the injury. V T of the pons was not significantly different for the two groups, and the control group values are in close agreement with those of Klumpers et al [20]. The lack of difference in pons V T provides further evidence that the pons remains a valid reference region following head injury.…”
Section: Limitationssupporting
confidence: 77%
See 3 more Smart Citations
“…Consequently, the findings of this study may not be relevant for reference tissue modelling of scans conducted within a few days of the injury. V T of the pons was not significantly different for the two groups, and the control group values are in close agreement with those of Klumpers et al [20]. The lack of difference in pons V T provides further evidence that the pons remains a valid reference region following head injury.…”
Section: Limitationssupporting
confidence: 77%
“…Although it has been reported that there is some specific binding in pons [31], the use of the pons as a reference tissue for [ 11 C]FMZ has been validated in controls [6,[18][19][20][21][22] and other neuronal conditions [20,21]. Head injury is known to result in damage across the brain, even in regions which appear structurally normal [7,32].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Data were reconstructed and analyzed as previously described (39), with one exception. Specifically, binding potential (BP ND ) was calculated using the simplified reference tissue model (40,41), with pons as the reference region (41). The following ROIs were delineated on the parametric BP ND image: frontal cortex, occipital cortex, temporal cortex, and cerebellum.…”
Section: Methodsmentioning
confidence: 99%